Implementing Circular Economy: International Experience and Policy Implications for Vietnam - Nam, Nguyen Hoang; Hanh, Nguyen Trong (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2019)
In recent years, the transition from traditional Linear Economy to Circular Economy has become a global trend. However, the implementation of each country may vary, with specific priorities. This paper aims at analyzing the concept of Circular Economy and some international experience of implementing Circular Economy. Accordingly, the Circular Economy is not a homogeneous model for the whole economy, but it includes plenty of different models built on the same philosophy, the philosophy of regeneration and restoration . Based on the international experience, some policy implications for Vietnam are discussed.